Long Distance Metabolic Regulation through Adipose-Derived Circulating Exosomal miRNAs: A Trail for RNA-Based Therapies? - Fatima, Farah; Nawaz, Muhammad (Frontiers in Physiology, 2017)
The contribution of non-coding RNAs, such as microRNAs (miRNAs) in regulating physiological and pathological states has been intensively elucidated during last 15 years. The discovery of circulating miRNAs (cir-miRNAs) in variety of body fluids, is, however a recent focus of interest in understanding pathophysiological states of their originating cells/organs. Yet another stimulating debate that takes miRNAs to the next level is their presence in exosomes, and this is truly interesting area of research. Exosomes are cell-derived extracellular vesicles, and are naturally equipped biological vehicles that not only enable functional transfer of miRNAs between cells (horizontal transfer) but also foster inter-organ communication, presumably guided by organ specific receptors—decorated on their surface. However, understandings on inter-organ communication elicited by tissue specific exosomal-miRNA fingerprints remain elusive. Recently, Thomou et al, has discovered that adipose tissue contributes a large fraction of adipose specific exosomal-miRNA fingerprints in blood circulation. Experimental evidence emphasise adipose tissue as major depot of cir-miRNAs that sail through blood flow and reach to distal organs—primarily in the liver, where they regulate gene expression of host tissue and elicit metabolic control. This appears to be a genetic form of adipokines (endocrine factors secreted from adipose tissue). We review this elegant study in the light of such offshore metabolic insults, and make an effort to address few important missing links between miRNAs and exosomes. We provide potential perspectives on how this knowledge could be steered towards monitoring complex metabolic diseases and beyond.